Energy Conservation as a Sustainable Strategy for Smart Home Buildings in Amman, Jordan with Improving Indoor Built Environment features and key performance - Awada, Emad A.; Abed, Amal; Radwan, Eyad; Al-Qaisi, Aws; Al-Rawashdeh, Ayman Y. (International Journal of Energy Economics and Policy, 2021)
As an ingenious efficient environment, smart buildings can be considered as essential constituents for energy conservation. That is, in today’s energy demands upsurges and energy sources degradation, the idea of the smart home building has a major implication on improving the living environment along with cutting down on energy consumptions. Therefore, this study investigates the energy conservation theme in Amman, Jordan in terms of opportunities and challenges vs. renewable energy technology. This study was based on interviews with the expert (academics, professionals architects, and electrical engineers, in addition to employees in Electrical companies) aiming to identify the problematic gap in designing theoretical analysis of a smart automated building based on collaboration work between Electrical and Architectural Engineering. From an Electrical Engineering point of view, automated control building systems can provide efficient means of comfort, sustainable habitat environment, and energy conservation as a building advantage. Such a scheme can be accomplished through automated control software (LabView), sensors, network infrastructure, logic design, and mechanical actuators. Meanwhile, from an architecture point of view, passive design strategies can reduce energy consumption along with public awareness for building users. This was implemented through simulation for base case building showing the integration between architectural and electrical systems through using a hybrid system. As a result, this new building automation design will help reducing energy consumption by controlling light fixtures, air-condition, water pumps, and many more appliances. The design guidelines, once formulated and enacted, will guarantee energy conservation qualitatively which will serve as a proposed guideline for enhancing buildings’ regulation and codes. Keywords: Energy Conservation, Sustainable Strategy, Smart Building, Indoor Built Environment. JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.11717